Removal of endotoxin by reverse phase HPLC abolishes anti-endothelial cell activity of bacterially expressed plasminogen kringle 5. (October 2003) - Dudley, Andrew; McKinstry, William; Thomas, David; Best, James; Jenkins, Alicia
The success of recombinant protein expression/purification in Escherichia coli depends on a high-fidelity system rendering purified proteins free of confounding contaminants such as endotoxin. Here we report on the expression and purification of a cryptic plasminogen-derived domain, kringle 5, which was previously reported to specifically inhibit endothelial cell growth and, therefore, angiogenesis. Using a histidine (HIS)-tag expression and Ni + -NTA agarose purification system identical to previous reports, we found that our purified recombinant kringle 5 did inhibit endothelial cell growth, but this activity could not be eradicated by heat denaturing or proteolysis of kringle 5 with various proteases. This led us to suspect the presence of a contaminant in the purified samples. Quantitative endotoxin testing using a limulus amoebocyte lysate assay revealed that all samples purified by Ni + -NTA agarose alone harbored high concentrations of endotoxin that could not be removed by additional purification on anion exchange chromatography. Finally, when kringle 5 was rendered endotoxin-free by purification on reverse phase high-performance liquid chromatography (HPLC), there was a complete loss of endothelial cell growth inhibitory activity. These results strongly suggest that endotoxin-free recombinant kringle 5 may not possess anti-angiogenic activity and demonstrates that, especially in angiogenesis type assays, endotoxin contamination can lead to a misinterpretation of results.